MESSAGE FROM THE DEAN - -, - (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
Let me first congratulate all the authors and contributors to the new edition of eJIR. I am sure that every new opportunity in coming months will lead to a better life in 2019. May the next edition of eJIR to be published in December 2018 brings more happiness, excitement and sweet surprises to your doorstep! Read more..